The Political Existence of Muslim Immigrants in The United Kingdom - Jeni Minan; Hanim Ismail; Mohamad Basri Bin Jamal; Dian Wahyu Danial (Journal of Government and Civil Society, 2025)
This paper examines the political existence of British Muslim immigrants amidst the negative Western perception of Islam. The approach used is descriptive qualitative with library research. This paper concludes that the negative image constructed by the West of Islam does not eliminate the political existence of British Muslim immigrants. This is evidenced by the election of Muslim politicians from both the Labour and Conservative parties to political positions in Britain, whether as mayors, members of parliament, or ministers. However, sentiment against Muslim immigrants cannot be eliminated because terrorist acts carried out by Muslim groups that do not represent Islam have an impact on Muslims themselves, who have actually grown and developed and enjoyed the freedom to practice their religion in Britain. These acts of terrorism are often described by Muslim scholars as foolishness. Artkel ini mengkaji eksistensi politik imigran Muslim Inggris di tengah persepsi negatif Barat terhadap Islam. Pendekatan yang digunakan adalah deskriptif kualitatif dengan metode studi pustaka. Makalah ini menyimpulkan bahwa citra negatif yang dibangun oleh dunia Barat terhadap Islam tidak menghapus eksistensi politik imigran Muslim di Inggris. Hal ini dibuktikan dengan terpilihnya politisi Muslim dari partai Buruh dan Konservatif ke posisi politik di Inggris, baik sebagai walikota, anggota parlemen, atau menteri. Namun, sentimen negatif terhadap imigran Muslim tidak dapat dihilangkan karena aksi terorisme yang dilakukan oleh kelompok Muslim yang tidak mewakili Islam berdampak pada umat Muslim sendiri, yang sebenarnya telah tumbuh dan berkembang serta menikmati kebebasan untuk menjalankan agama mereka di Inggris. Aksi terorisme ini sering digambarkan oleh para cendekiawan Muslim sebagai tindakan bodoh.